Visible light enhanced Cr(VI) removal from aqueous solution by nanoparticulated zerovalent iron - Montesinos, Victor Nahuel (2014)
Cr(VI) removal using nanoparticulated zerovalent iron is enhanced under visible light in comparison with the dark process. Using an Fe:Cr(VI) molar ratio (MR) of 1, 77% removal was obtained after two hours under irradiation, compared with 60% in dark conditions; use of MR 2 allowed almost total Cr(VI) removal. Experiments with selected filters indicated that active wavelengths are above 555 nm. The proposed mechanism involves a heterogeneous photocatalytic process promoted by the iron oxides present as an external layer of the nanoparticles acting as semiconductors after excitation with light, overcoming the passivation of the material taking place in the dark.